Resident consultant obstetrician presence on the labour ward versus other models of consultant cover: a systematic review of intrapartum outcomes - Henderson, J; Kurinczuk, JJ; Knight, M (BJOG : an international journal of obstetrics and gynaecology, 2017)
Background Several key policy documents have advocated 24‐hour consultant obstetrician presence on the labour ward as a means of improving the safety of birth. However, it is unclear what published evidence exists comparing the outcomes of intrapartum care with 24‐hour consultant labour ward presence and other models of consultant cover. Objectives To collate and critically appraise evidence of the effect of continuous resident consultant obstetrician cover on the labour ward on outcomes of intrapartum care compared with other models of consultant cover. Search strategy Studies were included which quantitatively compared intrapartum outcomes for women and babies where continuous resident consultant obstetric cover was provided with other models of consultant cover. Selection criteria Quantitative studies within healthcare systems with mixed obstetric‐midwifery models of care. Data collection and analysis Two researchers independently screened titles and full‐text publications, extracted data and assessed the quality of included studies. Meta‐analysis was performed using REVIEW MANAGER 5.3. Main results About 1508 publications were screened resulting in two papers, three conference s and one letter being included. All were single‐site time‐period comparison studies. The quality of studies overall was poor with significant risk of bias. The only significant finding in meta‐analysis related to instrumental deliveries, which occurred more frequently when there was on‐call consultant cover (unadjusted risk ratio 1.14; 95% CI 1.04–1.24). Conclusion No reliable evidence of the effects of 24‐hour resident consultant presence on the labour ward on intrapartum outcomes was identified. Tweetable More robust research is needed to assess intrapartum outcomes with resident consultant labour ward presence. Tweetable More robust research is needed to assess intrapartum outcomes with resident consultant labour ward presence.